(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Nickel titanium(NiTi) shape memory alloys have increased utilization for different engineering applications especially in biomedical applications .The aim of this study, first studied the powder metallurgy process variables such as compacting stress and sintering cycles on several physical tests such as x-ray diffraction, porosity and apparent density as well as mechanical tests such as microhardness, surface roughness , second studied the effect of alloying element of yttrium and tantalum on microhardness, surface roughness of NiTi shape memory alloys. Several alloys have been prepared by powder metallurgical technique. Vickers hardness, surface roughness measurements, XRD analysis, porosity and apparent density were performed. It was shown that the XRD diffraction tests of all samples have the same results of two phases at room temperature (RT) (monoclinic NiTi and hexagonal Ni3Ti).the result of adding tantalum in the percentage of (1%,2% and3%) in the expense of nickel, increasing hardness value gradually to record the highest value (310) HV at 3%.and also decrease the surface roughness from (0.36 to 0.15) µm at 3%Tantalum and 650 Mpa. While the result of adding yttrium in the percentage of (1%, 2% and3%) %Wt. in the expense of nickel, shown that the specimen of 2 % Yttrium and 650 Mpa compacting stress showed the hardness value of (275.7) HV .The hardness value decreases at 3 % and 1% additives at the same compacting stress to (272.26 and 200) HV respectively. The addition of Tantalum element decreases the surface roughness from (0.36 to 0.15) µm at 3%Tantalum and 650 Mpa .While the specimen of 2% Yttrium at 650 Mpa shown (0.16) µm surface roughness.